The male biological clock is ticking: a review of the literature - Pasqualotto, Fabio Firmbach; Borges Júnior, Edson; Pasqualotto, Eleonora Bedin (São Paulo Medical Journal, 2008)
The term biological clock is usually used by physicians and psychologists to refer to the declining fertility, increasing risk of fetal birth defects and alterations to hormone levels experienced by women as they age. Female fecundity declines slowly after the age of 30 years and more rapidly after 40 and is considered the main limiting factor in treating infertility. However, there are several scientifi c reports, chapters in books and review articles suggesting that men may also have a biological clock. The aim of our study was to conduct a review of the literature, based on the Medical Literature Analysis and Retrieval System Online (Medline), to evaluate the male biological clock. After adjustments for other factors, the data demonstrate that the likelihood that a fertile couple will take more than 12 months to conceive nearly doubles from 8% when the man is < 25 years old to 15% when he is > 35 years old. Thus, paternal age is a further factor to be taken into account when deciding on the prognosis for infertile couples. Also, increasing male age is associated with a signifi cant decline in fertility (fi ve times longer to achieve pregnancy at the age of 45 years). Patients and their physicians therefore need to understand the effects of the male biological clock on sexual and reproductive health, in that it leads to erectile dysfunction and male infertility, as well as its potential implications for important medical conditions such as diabetes and cardiovascular diseases.